If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(s + -4) = 3 Reorder the terms: 10(-4 + s) = 3 (-4 * 10 + s * 10) = 3 (-40 + 10s) = 3 Solving -40 + 10s = 3 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + 10s = 3 + 40 Combine like terms: -40 + 40 = 0 0 + 10s = 3 + 40 10s = 3 + 40 Combine like terms: 3 + 40 = 43 10s = 43 Divide each side by '10'. s = 4.3 Simplifying s = 4.3
| 10/3(10) | | 4e^3x-2=110 | | 2/3=7/x-4 | | -7-15x=23 | | 0.2+x=3 | | 2x+3y+6z=98 | | 60x=-32 | | 82=14+2x | | -5(7x+10)=-295 | | 3/4p=114 | | 26/x=13/8 | | y=x^2-17/2 | | 2c+5=3c | | 17x-4=4(4x+5)-16 | | 2c+5=8c | | 4c+6=6c | | 4c+6=6 | | 10x(8x^3+1)=0 | | log(x/5)=3 | | x+9=8+4 | | 32-5q=-100 | | 40x+65=325 | | x^2=4y-3+7 | | x+1=75 | | 2z-7=26 | | 6w-8=4(2w+5) | | 4c=5c-5 | | 6(54)-9y=-54 | | 9x-95=5x-7 | | -16=1x+11 | | 5(3x-1)=10x+5 | | Log(3x-1)+log(x-1)=6 |